Politicians' personal legacies from olympic bids and referenda: An analysis of individual risks and opportunities - Thomas Könecke; Michiel de Nooij (Journal of Risk and Financial Management, 2022)
The popularity of staging Olympic Games has dropped in democratic countries as a series of failed referenda and withdrawn bids as well as protests against mega sport events have shown in recent years. Nevertheless, the there still are democratically elected office-holders willing to become involved in an Olympic bid despite the high probability of public opposition and the threat of an almost unwinnable referendum. This conceptual study analyses the individual risk management that these politicians have to concern themselves with because of their involvement in Olympic bids and referenda. It does so by looking at possible 'personal legacies' the politicians can obtain. It is interesting to note that although the size of such legacies will vary, they can result irrespective of the outcome of a bid or a referendum and can have positive, negative, or neutral effects for the politician(s) in question. As will be shown, personal legacies can also be obtained by opponents of Olympic bidding ambitions, which is not the only finding that is problematic particularly for the IOC and National Olympic Committees interested in hosting Olympic Games or other sport events.
Keywords: 650; bidding process; legacy; mega sport event; Olympic bids; referendum